2016
DOI: 10.1080/14397595.2016.1206507
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of tocilizumab in achieving clinical and functional remission, and sustaining efficacy in biologics-naive patients with rheumatoid arthritis: The FIRST Bio study

Abstract: Objective: To evaluate effectiveness and safety of tocilizumab (TCZ) in biologic-naive Japanese patients with rheumatoid arthritis (RA) in real-world settings, and to analyze the relationship between disease duration and clinical outcomes. Methods: The FIRST Bio study was a postmarketing surveillance study of intravenous TCZ in biologics-naive patients who had a prior inadequate response or were intolerant to 1 conventional synthetic disease-modifying antirheumatic drug (csDMARD). Effectiveness, safety, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 45 publications
4
8
0
2
Order By: Relevance
“…In addition, patients in the present analysis with any change in corticosteroid dose had an overall reduction in daily dose from baseline to month 6 [mean (SD) change,  − 2.2 (9.0) mg]. Corticosteroid-sparing effects of TCZ have similarly been observed in other real-world studies of TCZ use in routine practice conducted in Japan [9], France [25, 26], Australia [27], Germany [28], and the USA [29]. Together, these findings show that both TCZ monotherapy and combination therapy reduce the need for corticosteroids in patients with RA.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, patients in the present analysis with any change in corticosteroid dose had an overall reduction in daily dose from baseline to month 6 [mean (SD) change,  − 2.2 (9.0) mg]. Corticosteroid-sparing effects of TCZ have similarly been observed in other real-world studies of TCZ use in routine practice conducted in Japan [9], France [25, 26], Australia [27], Germany [28], and the USA [29]. Together, these findings show that both TCZ monotherapy and combination therapy reduce the need for corticosteroids in patients with RA.…”
Section: Discussionsupporting
confidence: 65%
“…This pattern of decreased concomitant csDMARD use may be an indirect measure of the effectiveness of TCZ. The observational FIRST Bio study of biologic-naive patients with RA initiating TCZ also reported a reduction in both the proportion of patients receiving concomitant MTX and the MTX dose at month 6 [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При 24-месячном проспективном наблюдении нарастания риска СКИ не отмечено [43]. Тоцилизумаб В ходе РКИ и продолженных открытых исследований частота СКИ, развивавшихся у больных РА при лечении то-цилизумабом (ТЦЗ), колебалась в пределах 4,4-9,0 на 100 па-циенто-лет [44][45][46][47][48][49][50][51] и была аналогичной таковой у больных, получавших иФНОα. При увеличении суточной дозы с 4 до 8 мг/кг вероятность развития СКИ повышалась в 2,33 раза [52].…”
Section: анти-в-клеточные препаратыunclassified
“…В ходе РКИ и продолженных открытых исследований частота СКИ, развивавшихся при лечении тоцилизумабом (ТЦЗ), колебалась в пределах 4,4-9,0 на 100 пациенто-лет [29][30][31][32][33][34][35][36] и была аналогичной таковой у больных, получав-ших иФНО-α. При увеличении суточной дозы с 4 до 8 мг/кг вероятность развития СКИ повышалась в 2,33 раза [37].…”
Section: тоцилизумабunclassified